1999
DOI: 10.1037/0022-006x.67.6.847
|View full text |Cite
|
Sign up to set email alerts
|

Community services for rape survivors: Enhancing psychological well-being or increasing trauma?

Abstract: This research examined how contact with the legal, medical, and mental health systems affects rape survivors' psychological well-being. Although community services may be beneficial for some victims, there is increasing evidence that they can add trauma, rather than alleviate distress (termed secondary victimization). This study examined how secondary victimization affects rape survivors' posttraumatic stress (PTS) symptoms. Adaptive and snowball sampling were used to recruit a sample of 102 rape survivors. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
196
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(211 citation statements)
references
References 26 publications
9
196
0
1
Order By: Relevance
“…Layman, Gidycz, and Lynn's study of college women showed that acknowledged rape victims experienced more forceful assaults, resisted more, demonstrated clearer refusal to the attacker, and reported more PTSD symptoms (Layman et al, 1996). In a convenience sample of 102 communityresiding rape survivors (Campbell et al, 1999), neither victim demographics nor rape characteristics were associated with posttraumatic stress symptoms, but victims of known attackers who received few community services and experienced high secondary victimization postassault had more symptoms.Although the studies just reviewed have analyzed correlates of PTSD sequelae, few focused solely on adult female rape victims. Furthermore, none focused on characteristics of the recovery environment (e.g., support system responses), using a validated instrument, which also may be consequential for recovery (Ullman, 1999).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Layman, Gidycz, and Lynn's study of college women showed that acknowledged rape victims experienced more forceful assaults, resisted more, demonstrated clearer refusal to the attacker, and reported more PTSD symptoms (Layman et al, 1996). In a convenience sample of 102 communityresiding rape survivors (Campbell et al, 1999), neither victim demographics nor rape characteristics were associated with posttraumatic stress symptoms, but victims of known attackers who received few community services and experienced high secondary victimization postassault had more symptoms.Although the studies just reviewed have analyzed correlates of PTSD sequelae, few focused solely on adult female rape victims. Furthermore, none focused on characteristics of the recovery environment (e.g., support system responses), using a validated instrument, which also may be consequential for recovery (Ullman, 1999).…”
mentioning
confidence: 98%
“…Reactions from others may either reinforce and compound the culture's victim-blaming attitudes toward rape victims (e.g., rape myths) or contradict this ideology by believing and supporting victims, and defining rape as a violent crime. Symonds (1980) has argued that "secondary victimization," which refers to the blame, disbelief, and stigmatizing responses that others make to victims, is commonly experienced by rape (Campbell et al, 1999;Davis, Brickman, & Baker, 1991;McAuslan & Abbey, 1998;Ullman, 1996a). Furthermore, some data suggest that social reactions may affect victim coping and subsequent recovery from sexual assault (Ullman, 1996a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Responses to trauma survivors in the literature reveal that their experiences are relatively negative, both within the legal and medical systems [13][14][15]. Survivors often find that the criminal justice system has outcomes quite unfavorable to them; most sexual assault cases are never prosecuted, and, on average, in 12 percent of reported cases the offender is convicted [16].…”
Section: Patient-centered Responsementioning
confidence: 99%
“…The types of secondary victimisation are victim blaming, inappropriate language or conduct by the police, medical professionals and by other organisations that have access to the victim after their experience of crime. This conception of secondary victimisation is also evident in cases of female rape; it was found that many female rape victims feel as if the experience of seeking help from mental, medical, and legal health systems only exacerbates the trauma (Campbell et al, 1999). This study explored the link between posttraumatic stress symptoms (PTSS) and secondary victimisation.…”
Section: Emphasis Added)mentioning
confidence: 99%